How the endocrine system works - Neal, J. Matthew
"How the Endocrine System Works is not another standard introduction to endocrinology, but an innovative and fun way to learn about the importance of the key glands in the human body and the hormones they control. It is explained in 9 easy-to-understand lectures, with additional material on the treatment and management of endocrine disorders. How the Endocrine System Works: - Is designed for those in need of a concise introduction to this fascinating area of medicine - Has been rigorously updated to reflect today's endocrinology teaching - Includes more focus on the treatment and management of endocrine disorders - Features more on evidence-based medicine, obesity, epidemiology, and biostatistics - Includes summaries of key research which affects diagnostic criteria - Includes brand new case-based review questions at the end of each chapter - Features full-color diagrams throughout How the Endocrine System Works is the perfect introduction for all medical students, as well as for students of bioscience, and other healthcare disciplines"--
Machine generated contents note: Acknowledgements How to Use This Book Lecture 1. An Overview Lecture 2. Pituitary and Hypothalamus Lecture 3. The Thyroid Lecture 4. Adrenal Gland Lecture 5. Glucose Metabolism Lecture 6. Calcium Metabolism Lecture 7. Reproductive Endocrinology Lecture 8. Lipid Disorders Lecture 9. Disorders of Multiple Endocrine Glands and Paraneoplastic Syndromes Appendix: Clinical trials, evidence-based medicine, and reading the literature Glossary Index .
Includes bibliographical references and index.
Keywords: Endocrine glands; Endocrine glands; Hormones; MEDICAL / Endocrinology & Metabolism